Changes in Perceived Egocentric Direction during Symmetric Vergence. (February 2013) - Sridhar, Deepika; Bedell, Harold E
The Wells–Hering's laws of perceived egocentric visual direction (EVD) assume that information about eye position includes equal contributions from both eyes. An implication of this assumption is that only versional eye movements should lead to a change in perceived EVD. Previously, we showed that a differential weighting of eye-position information occurs in some individuals during asymmetric vergence. To extend this finding, we determined here whether a differential weighting of eye-position information occurs also during symmetric vergence eye movements. Open-loop pointing responses to a bright target were obtained in five subjects to estimate the contribution of each eye's position information to perceived EVD during symmetric vergence demands that ranged from 6 prism diopters base in to 18 prism diopters base out. In all five subjects, the slopes of the lines fit to the pointing responses were in the direction that was predicted from an unequal weighting of eye-position information. We conclude that symmetric vergence movements can result in a change in perceived visual direction, contrary to an assumption of the Wells–Hering's laws.